Кордони в художніх творах Григора Тютюнника - Звягіна, Ганна Олександрівна; Zviahina, H. O. (My University, 2017)
У статті розглядається творчість Григора Тютюнника крізь призму етнопсихології, зокрема тема відображення війни і повоєнного часу, змін у свідомості людей під впливом цих подій, створення кордонів у свідомості дорослих людей. Увагу зосереджено на мовних засобах, завдяки яким вона відображена. Досліджено поняття «розмивання кордонів» і зміни, які є його наслідком. Відзначено різні способи реакції людей та їхньої поведінки у межовій ситуації війни. The works by Hryhor Tiutiunnyk are examined through the prism of ethnic psychology, in particular, the theme of reflection of war and post-war time, changes in the minds of people under the influence of these events, creating borders in the minds of adult people. The focus is made on the linguistic resources, through which it is reflected. The concept «blurring boundaries» and the changes that are its consequence are studied. Different ways of reactions of people and their behavior in boundary situations of war are noted. The author comes to the conclusion that the national character is the specific combination of human traits with specific historical and social-economic conditions of the existence of the nation. The border situation allows demonstrating the best of ethnic and psychological traits of the Ukrainians, forced to redefine themselves, to open something new, to feel oneness with all people. The war is reflected in the works of the author, because he was a witness of those events, a milestone that changes people forever. Some of the characters lose themselves, some perceive it as a way of earning, but for most it is a test on humanity, on kindness.
Borders in the Works by Hryhor Tiutiunnyk
Keywords: кордон; розмивання кордонів; етнопсихологія; самоідентифікація; трансформація свідомості; межова ситуація; border; blurring boundaries; ethnic psychology; selfidentity; transformation of consciousness; boundary situations